Book review of “Biomagnetics: Principles and Applications of Biomagnetic Stimulation and Imaging” edited by Shoogo Ueno and Masaki Sekino - Riu, Pere J. (Biomed Eng Online, 2016)
This article is a review of the book “Biomagnetics: Principles and Applications of Biomagnetic Stimulation and Imaging” (ISBN 978-1-4822-3920-1, 343 pages) edited by Shoogo Ueno and Masaki Sekino published by CRC Press, Taylor and Francis Group, LLC in 2015. The content of the book and its importance for biomedical engineering have been discussed in this invited review.